Studies of the Taxine From the Needles of the Moroccan Yew - Chakchak, Hind; Zineddine, Hamid; Chaouch, Aziz (Asian Journal of Chemistry, 2012)
The taxine, alkaloids precursor of the taxol, have been isolated from the needles of the Moroccan yew (Taxus baccata) and characterized through the use of high performance liquid chromatography. The taxine B, isotaxine B and taxoide basique 2-deacetyltaxine A were identified by gas chromatography and mass spectrometry.